2014
DOI: 10.1111/jon.12171
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse and Focal Corticospinal Tract Disease and Its Impact on Patient Disability in Multiple Sclerosis

Abstract: Background and Purpose We investigated the impact of focal and diffuse corticospinal tracts damage on sensory-motor disability in multiple sclerosis (MS) patients. Methods Twenty-five MS patients underwent 3.0 Tesla (3T) magnetic resonance imaging with diffusion tensor imaging (DTI). The Expanded Disability Status Scale (EDSS) and the Timed 25-Foot Walk test (T25FW) quantified patient physical disability. Fractional anisotropy (FA) and mean diffusivity (MD) of the corticospinal tracts, whole brain and cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
0
30
1
Order By: Relevance
“…Conversely, such correlation between DTI parameters and EDSS has been previously reported in cross-sectional studies (Daams et al, 2015;Tovar-Moll et al, 2015).…”
Section: Edss Median (Range)mentioning
confidence: 57%
“…Conversely, such correlation between DTI parameters and EDSS has been previously reported in cross-sectional studies (Daams et al, 2015;Tovar-Moll et al, 2015).…”
Section: Edss Median (Range)mentioning
confidence: 57%
“…34 The PLIC FA reported in Table 2 is slightly higher than in that study and another tract-based CST analysis, though the standard deviations are similar. 32, 34 Our PLIC ROIs were carefully inspected to ensure anatomical accuracy, but it is possible that our ROI-based measure does not fully capture diffusion along the CST. Both tract-based CST studies showed a relationship between diffusion and EDSS.…”
Section: Discussionmentioning
confidence: 99%
“…Walking performance has been associated with DTI (Naismith et al, 2013) and MTR (Zackowski et al, 2009) of the lateral columns in MS. T25FW performance (Tovar-Moll et al, 2015, Klineova et al, 2016, Hubbard et al, 2016) and walking velocity and endurance (Hubbard et al, 2016) were related to DTI measures, while both total EDSS and Functional Systems Score (FSS) pyramidal scores were related to FA of the brain CST measured from the pons to the cortex (Tovar-Moll et al, 2015), and total EDSS score was also correlated with cervical spinal cord area (Bernitsas et al, 2015). However, controls were not included in these studies, and relationships of quantitative measures of strength and walking to brain MTR have not been explored, and DTI of the whole-brain CST from medulla to cortex in relation to function is lacking in MS.…”
Section: Introductionmentioning
confidence: 99%